The study of housing preferences of the Seletar community in Johor Bahru, Malaysia - Mohd Noordin, Muhammad Faiz; Abdullah, Fadzidah; Asif, Nayeem (2020)
Johor Johor Bahru, in the state of Johor, is located at the southern tip of Peninsular Malaysia and considered to be one of the most rapidly developing cities in Asia. The land resources of Johor Bahru is financially attractive to both local or foreign investors because of its emergent economic corridor, that is being led by the Iskandar Regional Development Authority (IRDA). The impacts of rapid development in this economic corridor has affected some of its Indigenous community groups, especially the Orang Seletar community. The Orang Seletar people, sea nomads of the Tebrau Strait shores, have been particularly exposed to cultural decay due to the surrounding rapid urbanization. This paper aims to consider the Orang Seletar’s culture and housing typology preferences to inform options for their future housing design consideration and to ensure their cultural sustainability. The first objective of the research is to examine culture and daily activities that were and continue to be practiced by the Orang Seletar, who used to live in houseboats and thus integral to their sea nomadic lifestyle. The second objective is to investigate the typology of the housing settlement patterns of the Orang Seletar community, and the third objective is to assess the housing settlement preferences of the Orang Seletar community. This research uses both qualitative and quantitative approaches, where content analysis of literature is utilised to achieve the first objective. Field observation and survey questionnaires techniques were used to achieve the second objective, and a structured interview was carried out to achieve the third objective. Three types of houses were identified in eight selected villages studied including: single storey landed brick houses that are built on the land by government; houses on stilts that are made of timber; and, lastly, raft houses that float on sea and reverine water. Based on this comparative study, it is concluded that the Orang Seletar people preferred to continue to live on raft houses.